The impact of technology on regional price dispersion in the US - Genc, Ismail H. (Technological and Economic Development of Economy, 2021)
We analyze the behavior of inflation in the era of fast pace information thanks to technological advances, especially internet. Owing to readily available information, prices/inflation should quickly converge under perfect competition. To this end, we explore the possibility of price convergence in regional inflation in the USA including the permanency of such a phenomenon if observed, a concern for monetary policy makers. Empirically, we analyze standard deviation of regional inflation with special attention to technology. We show that standard deviation of inflation is not constant over time, but not necessarily ever-declining. Technology seems to help reduce price dispersion across regions. First published online 12 October 2021